The Practicality of a Chemistry Learning Module on Hydrocarbon Topic Based on Guided Inquiry - Mulia, Vivi Sri (The Future of Education Journal, 2025)
Chemistry instruction in high schools still tends to emphasize the product aspect of knowledge while neglecting the scientific process, which is essential for developing students’ conceptual understanding. The lack of process-oriented instructional materials also contributes to students’ low process skills. To address this issue, this study aims to develop a guided inquiry-based chemistry learning module on the topic of hydrocarbons and to evaluate its practicality in classroom learning. This research employed the 4-D development model (Define, Design, Develop, Disseminate) involving expert validation and field testing. The research subjects were tenth-grade high school students. Data were collected through teacher and student response questionnaires and analyzed using descriptive statistics and Cohen’s Kappa formula. The results showed that the developed module demonstrated a very high level of practicality, with a Kappa value of 0.85 from teachers and 0.82 from students. These findings indicate that the guided inquiry-based module is effectively applicable in chemistry instruction and supports students in constructing conceptual understanding independently. Therefore, the module can serve as a practical alternative instructional resource that enhances meaningful chemistry learning.